Science experiments - Winston, Robert M. L.; Finch, Jenny Graham, Ian Goldsmith, Mike Burke, Lisa (Dorling Kindersley London, 2011)
Introduce your child to science with Professor Robert Winston's Science Experiments. These exciting hands-on experiments - from creating balloon rockets or glow-in-the-dark jelly to making metal detectors - will help your child get to grips with science. Science Experiments covers all areas from life on earth to physical science. There are projects for all abilities, from quick-and-easy science in seconds to trickier group projects for schools